The Impact of Indonesia Sovereign Credit Rating Upgrades and Investment Grade Status on the Sovereign Spread Changes - Novianti, Dwi Anggi; Danarsari, Dwi Nastiti (The Indonesian Capital Market Review, 2013)
Getting sovereign credit rating upgrades and achieving investment grade status are main goals for countries in order to gain lower yield spread and cost of borrowing. By using ordinary least square method, this research is aimed to analyze the impact of Indonesia sovereign credit rating up-grade and investment grade status on sovereign spread changes. The result shows that the sovereign credit rating upgrades within speculative grade category and investment grade status for Indonesia do not significantly impact sovereign spread reduction. On the other hand, the global condition, especially global risk appetite, has significant impact to Indonesia sovereign yield spread. The research also indicates that Indonesia macroeconomic fundamentals do not significantly explain the movement of sovereign yield spread.